Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Bacteria-mediated precursor-dependent biosynthesis of superparamagnetic iron oxide and iron sulfide nanoparticles - Bharde, Atul A.; Parikh, Rasesh Y.; Baidakova, Marina; Jouen, Samuel; Hannoyer, Beatrice; Enoki, Toshiaki; Bhagavatula L. V. Prasad; Shouche, Yogesh S.; Ogale, Satishchandra B.; Sastry, Murali (Langmuir, 2008)
The bacterium Actinobacter sp. has been shown to be capable of extracellularly synthesizing iron based magnetic nanoparticles, namely maghemite (gamma-Fe2O3) and greigite (Fe3S4) Under ambient conditions depending on the nature of precursors used. More precisely, the bacterium synthesized maghemite when reacted with ferric chloride and iron sulfide when exposed to the aqueous solution of ferric chloride-ferrous sulfate. Challenging the bacterium with different metal ions resulted in induction of different proteins, which bring about the specific biochemical transformations in each case leading to the observed products. Maghemite and iron sulfide nanoparticles show superparamagnetic characteristics as expected. Compared to the earlier reports of magnetite and greigite synthesis by magnetotactic bacteria and iron reducing bacteria, which take place strictly under anaerobic conditions, the present procedure offers significant advancement since the reaction occurs under aerobic condition. Moreover, reaction end products can be tuned by the choice of precursors used.

Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer

Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.

Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation